Patterns of splenic arterial enhancement on computed tomography scan are related to portal venous hypertension. Issue 5 (May 2020) - McCormick, Peter Aiden; Docherty, James R.
Abstract : Objectives: We have previously shown that patterns of splenic arterial enhancement on computed tomography scan change following liver transplantation. We suggested that this is related to changes in portal venous pressure. The aim of this study was to see if similar patterns occur in patients with and without portal hypertension and in patients before and after portal systemic shunts (transjugular portosystemic shunts). Methods: We evaluated contrast enhanced computed tomography scans in patients being evaluated for liver disease and compared those from patients with and without portal hypertension. In addition we evaluated patients who had computed tomography scans before and after transjugular portosystemic shunts shunts. Splenic arterial enhancement was evaluated using Hounsfield units (pixel counts). Results: Twenty-four patients with clinically significant portal hypertension were compared to 91 without. Mean splenic pixel count was significantly lower in patients with clinically significant portal hypertension (88.2 ± 17.7 vs. 115.2 ± 21.0; m ± SD, P < 0.01). Computed tomography scans were available in 18 patients pre- and post-transjugular portosystemic shunts. Pixel counts were significantly higher in the post-transjugular portosystemic shunts scans (99.7 ± 20.9 vs. 88.9 ± 26.3; P < 0.05). Conclusion: This study supports the hypothesis that changes in portal venous pressure are related to changes in splenic arterial enhancement. We suggest that this reflects changes in the splenic micro-circulation. This mechanism may be part of the innate immune response and may also be important in the pathogenesis of hypersplenism.